Penilaian Karakteristik Lahan untuk Kedelai di Kabupaten Bireuen - Abubakar Karim; Sugianto Sugianto; Siti Hajar (Fakultas Pertanian, Universitas Syiah Kuala, 2008)
Assesments of Land Characteristics of Soybean at Bireuen DistrictABSTRACT. Bireuen district has been known as soybean production centre in Aceh Province. However, average yield obtained is still under national yield. This research aimed: (1) to find out a relationship between land suitability and soybean yield, (2) to evaluate a relationship between land characteristics and soybean yield, (3) to determinate the land characteristics as determinable factor for soybean yield. There were nine characteristics sites were used under soybean farming that have land heterogeneity among sites and homogeneity within sites: 4 under rice field and 5 under rainfed. Natures of land morphology was evaluated each sites, and then soil samples were taken for soil properties evaluation in laboratory. The parameter of land morphology properties, physical and chemical were then adjusted according to the need of land suitability for soybean. Level of land management and its yield done by farmers were also evaluated. Yield from each plot (2 x 3 m2) was at random determined. The land suitability class was determined by comparing the land characteristics/land quality with soybean growth specification. Criteria made by Agriculture Department was used as a guidance. Futhermore, in order to determine determinable land characteristics were arranged in multiple linear regression analyses, in which yield of soybean as a Y and land characteristics as a X. Research result showed that the class of land suitability established were in parallel with soybean yields measure under relatively good management plots. Of the land characteristics that can be used as determinable factor were slope, rainfall, texture, drainage, and nutrient storage (pH). A multiple linear regression equation was established for soybean yield as follow: Y= -1.133 – 0.018X1 + 0.001X2 – 0.001X3 + 0.009X4 + 19.555X5 + 0.025X6 + 0.781X7 – 0.019X8; R2= 0.98, where : X1 = slope, X2= soil susceptibility to erosion, X3= rainfall, X4= sand fraction, X5= N-total, X6= P-available, X7= K-exchange, X8= base saturation, and R2= determination coefficient.